Remarks on Receiving the Distinguished Service Award - Alice Horowitz, PhD (Blackwell Synergy, 2000)
Alex, thank you very much for your eloquent introductory remarks. I am overwhelmed and nearly speechless. I truly am honored to receive this award because it bestows an unparalleled recognition by my colleagues with whom I have worked for over 30 years